Political familism: problems of conceptualization and internal mechanisms of phenomena - Самброс, А. С. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
This article analyzes the types of political familism and internal mechanisms of its installation, functioning and restoration in political regimes. It studies the comparative relationship between political and immoral familism. Much attention is paid to the patterns of political familism in mass culture and possibilities of their analytical use in political science.